Approaches for esophagectomy for esophageal cancer: a network meta-analysis - Gomes dos Santos Ferreira Rebelo, Artur Luis; Wadewitz, Elisabeth; Sunami, Yoshiaki; Friedrichs, Juliane; Grilli, Maurizio; Vey, Johannes; Klose, Johannes; Bayram, Onur; Merling, Marie; Kleeff, Jörg H.; Ronellenfitsch, Ulrich (European journal of surgical oncology, 2025)
Introduction - Esophageal cancer remains a leading cause of cancer-related mortality worldwide. Esophagectomy is the cornerstone of curative treatment, but the optimal surgical approach remains debated. Newer techniques such as hybrid esophagectomy, minimally invasive esophagectomy (MIE), and robot-assisted minimally invasive esophagectomy (RAMIE) have been developed to improve perioperative outcomes while maintaining oncologic efficacy. We aim to compare the effects of open, hybrid, minimally invasive, and robot-assisted approaches to esophagectomy on survival and perioperative outcomes in patients with esophageal cancer. - Methods - A systematic review and network meta-analysis (NMA) were conducted, including 10 reports from 6 randomized controlled trials identified via PubMed, Cochrane Library, Embase, CINAHL, ClinicalTrials.gov, and ICTRP. Comparative analyses between open esophagectomy (OE), hybrid laparoscopy-thoracotomy (HYB LapS-ThoT), MIE, and RAMIE were performed using random-effects NMA models. Hazard ratios (HR), odds ratios (OR), and mean differences (MD) were calculated for outcomes. - Results - There were no significant differences in overall survival among OE, HYB LapS-ThoT, MIE, and RAMIE. Pulmonary complications were significantly lower with MIE (OR 0.47, 95 % CI 0.33-0.69, p < 0.0001) and RAMIE (OR 0.39, 95 % CI 0.27-0.57, p < 0.0001) compared to OE. RAMIE yielded a higher lymph node harvest (MD 1.56, 95 % CI 0.58-2.54, p = 0.002) and lower reoperation rates (OR 0.65, 95 % CI 0.45-0.93, p = 0.020) than OE. HYB LapS-ThoT was associated with increased anastomotic leakage compared to OE (OR 1.66, 95 % CI 1.02-2.69, p = 0.041). - Conclusion - MIE and RAMIE significantly reduce pulmonary complications without compromising survival. Hybrid approaches appear to increase the risk of anastomotic leakage. These findings support minimally invasive techniques, especially RAMIE; however, more evidence and further studies are needed to allow for a clearer and more definitive conclusion.
Online verfügbar: 21. Oktober 2025, Artikelversion: 28. Oktober 2025
Gesehen am 01.12.2025